The Comprehensive Counseling Center Model. Issue 4 (2nd October 2017) - Brunner, Jon; Wallace, David; Keyes, Lee N.; Polychronis, Paul D.
ABSTRACT: The authors outline a four-factor model and philosophy for college mental health services that addresses the loss of comprehensiveness in some centers due to changes in organizational structure. Given research on demand for services and retention of those seen in centers, emphasis is placed in particular upon the value of consultation, outreach, and training work across the entire campus community. The model challenges some assumptions made by proponents of integrated care, including its definition, and illustrates the benefits of establishing and maintaining a fully comprehensive college counseling service.